Comparison of the skin biophysical parameters of Southeast Asia females: forehead–cheek and ethnic groups. (6th December 2012) - Lee, M.R.; Nam, G.W.; Jung, Y.C.; Park, S.Y.; Han, J.Y.; Cho, J.C.; Suh, K.D.; Hwang, J.K.
Abstract Background Regional and ethnic (racial) differences in skin properties are well known. However, regional and racial studies are limited and have studied skin properties using an insufficient number of subjects and limited ethnic groups, except in the case of some recent studies. Objective The aim of this study was (1) to compare the skin biophysical parameter among the large scale of Southeast Asia females group and (2) to compare skin properties of the forehead and cheek. Methods We measured and compared seven skin biophysical parameters, such as skin hydration, sebum, skin pH, melanin index, erythema index, skin elasticity and transepidermal water loss (TEWL), of the forehead and cheek of a large population of Indonesian (n = 200), Vietnamese (n = 100) and Singaporean females (n = 97). Results At the point of site difference, there were significant differences in five biophysical parameters (skin hydration, skin pH, melanin index, erythema index and skin elasticity) in Indonesian females. In Vietnamese and Singaporean women, they were significant differences in five biophysical parameters (skin hydration, skin pH, melanin index, erythema index and TEWL). At the point of ethnic difference, the Indonesian women had the highest skin pH and melanin index between the different ethnic groups. Vietnamese women had the highest skin hydration and TEWL in the forehead, whereas Singaporean women had the highest skin elasticity. Conclusion The skin biophysical parameters are different between the forehead and cheek among Southeast Asian females. It also reveals that the biophysical parameters are different in same racial group.